2021
DOI: 10.1177/17562872211002059
|View full text |Cite
|
Sign up to set email alerts
|

Reviewing the evidence for shockwave- and cell-based regenerative therapies in the treatment of erectile dysfunction

Abstract: Erectile dysfunction (ED) is both a common and complex disease process. Existing ED treatments do not always achieve adequate results. There is clinical interest in employing regenerative therapies, including low-intensity extracorporeal shockwave therapy (Li-ESWT), platelet rich plasma (PRP), and stem cell therapy (SCT), in the treatment of ED as adjunct or alternative treatments. Here, we present evidence for emerging shockwave- and cell-based regenerative therapies for the treatment of ED following a thorou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 98 publications
2
9
0
Order By: Relevance
“…The PRP‐treated group exhibited a significantly greater number of preserved myelinated cavernous neural axons at 1 month as compared to the non‐PRP‐treated group. These results support the conclusion that PRP increases the number of myelinated axons, thus facilitating the recovery of erectile function (Drury et al., 2021; Raheem et al., 2020). Similarly, the Group 2 patients in our study reported that in repeated PRP injections, the sensation of sensitivity and pain in the penile area increased as compared to the previous injection, despite application of the same local anaesthetic.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The PRP‐treated group exhibited a significantly greater number of preserved myelinated cavernous neural axons at 1 month as compared to the non‐PRP‐treated group. These results support the conclusion that PRP increases the number of myelinated axons, thus facilitating the recovery of erectile function (Drury et al., 2021; Raheem et al., 2020). Similarly, the Group 2 patients in our study reported that in repeated PRP injections, the sensation of sensitivity and pain in the penile area increased as compared to the previous injection, despite application of the same local anaesthetic.…”
Section: Discussionsupporting
confidence: 88%
“…The PRP-treated group exhibited a significantly greater number of preserved myelinated cavernous neural axons at 1 month as compared to the non-PRP-treated group. These results support the conclusion that PRP increases the number of myelinated axons, thus facilitating the recovery of erectile function (Drury et al, 2021;Raheem et al, 2020).…”
Section: Ta B L E 3 Comparison Of the Mean Iief-ef Score Increase Between Groups Based On Ed Gradessupporting
confidence: 88%
See 1 more Smart Citation
“…Thus, although the mechanism of action of stem cells in the treatment of ED in cavernous nerve injury is becoming clear, there is still controversy about the possible role of stem cells in the treatment of ED without an acute pathogenetic cause. Some of the stem cell studies described above also illustrate an exciting avenue for regenerative medicine between gene therapy and stem cell applications, as stem cells are increasingly being used as vectors to deliver genes to desired tissues [ 58 , 59 ].…”
Section: Stem Cell Therapy (Sct)mentioning
confidence: 99%
“…Following the seminal work of Vardi et al demonstrating the applicability of Li-ESWT in andrology [7,8], there is accruing evidence of the therapeutic benefit of Li-ESWT in patients with ED [8][9][10]. Previous studies have associated the observed therapeutic benefit with the intrinsic ability of Li-ESWT to up-regulate growth factors, promote endothelial progenitor cell proliferation and activation, induce neovascularization, increase the production of nitric oxide, elicit tissue reperfusion and regeneration, and consequently improve erectile function [11][12][13].…”
Section: Introductionmentioning
confidence: 99%